New material and design concepts for constructions of vehicles – challenges for thermal an cold joining techniques - Meschut, Gerson; Goede, M. (Tagungsband zur 9. International Aachen Welding Conference: Joining in Traffic and Transportation Industry – Processes, Progress, Applications)

Kleben und Hybridfügen von Leichtbaustrukturen für den Automobilbau - Disse, T.; Maciej, M.; Meschut, Gerson; Piccolo, S.; Timmermann, R.; Wibbeke, T.-M. (Adhäsion)

Mechanische Fügetechnik für die Mischbauweise – Teil 1: Systemoptimierungen - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Material-Secific joining techniques for magnesium body structures - Hahn, O.; Schumann, S.; Meschut, Gerson; Fuhrmann, T.

Mechanische Fügetechnik für die Mischbauweise – Teil 2: Neuartige Fügeverfahren - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)

A Distributed Hash Table for Computational Grids - Riley, Chris; Scheideler, Christian (IPDPS)

Zukünftige Werkstoff- und Bauweisenkonzepte im Automobilbau - Herausforderungen für die Gewindetechnologie - Meschut, Gerson (Tagungsband zum 2. Böllhoff-Fachkolloquium)

Fügen von Kunststoffen im strukturellen Leichtbau - Bye, C.; Draht, T.; Küting, J.; Lübbers, R.; Meschut, Gerson; Ruther, M. (Tagungsband zum 11. Paderborner Symposium Fügetechnik „Mechanisches Fügen und Kleben“)

Robust Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (IPTPS)

Druckfügeverfahren und damit hergestellte Rahmen - Hahn, O.; Meschut, Gerson

Fügeverfahren und Fügevorrichtung zum Verbinden von überlappend angeordneten Fügeteilen - Amedick, Jürgen; Hahn, Ortwin; Kurzok, Jan; Letsch, Stefan; Meschut, Gerson; Peitz, Volker; Timmermann, Rüdiger

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IWIA)

The hyperring: a low-congestion deterministic data structure for distributed environments - Awerbuch, Baruch; Scheideler, Christian (SODA)

Consistent and compact data management in distributed storage systems - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Pagoda: a dynamic overlay network for routing, data management, and multicasting - Bhargava, Ankur; Kothapalli, Kishore; Riley, Chris; Scheideler, Christian; Thober, Mark (SPAA)

The effect of faults on network expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (SPAA)

math-kit - Ein multimedialer Baukasten für die Mathematikausbildung im Grundstudium - Unger, L.; Bauch, M.; Baudry, A.; Bungenstock, M.; Mertsching, B.; Oevel, Gudrun; Padberg, K.; Thiere, B. (SoftwareTechnikTrends)

V:Drive - Costs and Benefits of an Out-of-Band Storage Virtualization System - Brinkmann, André; Heidebuer, Michael; Meyer auf der Heide, Friedhelm; Rückert, Ulrich; Salzwedel, Kay; Vodisek, Mario (21st IEEE Conference on Mass Storage Systems and Technologies / 12th NASA Goddard Conference on Mass Storage Systems and Technologies, Greenbelt, Maryland, USA)

Optical properties of planar metallic photonic crystal structures: Experiment and theory - Christ, A.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S. G.; Gippius, N. A.; Giessen, H. (Physical Review B)

Tailoring the Ultrafast Dephasing of Quasiparticles in Metallic Photonic Crystals - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Giessen, H. (Physical Review Letters)

Wolff, Christian Freiherr von - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 3: Men–Z)

Smoothed Number of Extreme Points under Uniform Noise - Sohler, Christian; Damerow, Valentina (Proceedings of the 20th European Workshop on Computational Geometry (EWCG'04))

Extreme Points Under Random Noise - Damerow, Valentina; Sohler, Christian (Proceedings of the 12th European Symposium on Algorithms (ESA'04))
Given a point set P in the d-dimensional unit hypercube, we give upper bounds on the maximal expected number of extreme points when each point is perturbed by small random noise chosen independently for each point from the same noise distribution Δ. Our results are parametrized by the variance of the noise distribution. For large variance we essentially consider the average case for distribution Δ while for variance 0 we consider the worst case. Hence our results give upper bounds on the number of extreme points where our input distributions range from average case to worst case. Our main contribution is a rather general lemma that can be used to obtain upper bounds on the expected number of extreme points for a large class of noise distributions. We then apply this lemma to obtain explicit bounds for random noise coming from the Gaussian normal distribution of variance σ² and the uniform distribution in a hypercube of side length &epsilon. For these noise distributions we show upper bounds of O( (1/ σ )^d * log^3/2 * d - 1 n ) and O( ( (n log n) / ε )^d/(d+1) ), respectively. Besides its theoretical motivation our model is also motivated by the observation that in many applications of convex hull algorithms the input data is inherently noisy, e.g. when the data comes from physical measurement or imprecise arithmetic is used.

Reducing State Changes with a Pipeline Buffer - Sohler, Christian; Krokowski, Jens; Räcke, Harald; Westermann, Matthias (Proceedings of the Vision, Modeling, and Visualization Conference (VMV 2004))
A limiting factor in the performance of a render- ing system is the number of state changes, i.e., changes of the attributes material, texture, shader program, etc., in the stream of rendered primitives. We propose to include a small buffer between appli- cation and graphics hardware in the rendering sys- tem. This pipeline buffer is used to rearrange the incoming sequence of primitives on-line and locally in such a way that the number of state changes is minimized. This method is generic; it can be easily integrated into existing rendering systems. In our experiments a pipeline buffer reduces the number of state changes by an order of magnitude and achieves almost the same rendering time as an optimal, i.e., presorted, sequence without pipeline buffer. Due to its simple structure and its low mem- ory requirements this method can easily be imple- mented in software or even hardware.

Sublinear-Time Approximation for Clustering via Random Sampling - Sohler, Christian; Czumaj, Artur (Automata, Languages and Programming (ICALP))

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo
2. Auflage 2006

Channel Adaptive Techniques in the Presence of Channel Prediction Inaccuracy - Aguiar, Ana; Karl, Holger; Wolisz, Adam (Proceedings of European Wireless 2004, Barcelona / Spain)

Einleitung „in der zeit“ – kunst aus sachsen-anhalt 2004 - Seng, Eva- Maria (Katalog der Landeskunstausstellung Sachsen-Anhalts in Magdeburg 2004)

Götter in der Stadt oder: „Wo Aas ist, sammeln sich die Geier!“ Stadtuntergänge bei Brecht und Trolle - Eke, Norbert Otto (Mahagonny.com. The Brecht Yearbook 29)

Intermedialität und Theatralisierung: Peter Greenaways Film-Theater - Eke, Norbert Otto (Crossing Media. Theater – Film – Fotografie – Neue Medien)

Eingebunkert – Stalin/Hitler: eine Konfiguration - Eke, Norbert Otto („Der Text ist der Coyote“. Heiner Müller Bestandsaufnahme)

Stressmodelle und Analyse der Hirntätigkeit - Weiß, M; Barthel, T; Baumeister, Jochen (ForschungsForum)

Teaching Object-Oriented Concepts with Eclipse - Meyer, Matthias; Wendehals, Lothar (Proc. of the Eclipse Technology eXchange Workshop (ETX), Satellite Event of the 19th Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA), Vancouver, Canada)
Object-oriented software development is a subject area difficult to teach, espcially to beginners. They face a lot of abstraction and (from a beginners point of view) isolated topics, such as the syntax and semantics of a programming language, the functionality of a software development environment and basic object-oriented concepts. Although many professionals in education believe in the ``object first'' approach as the best method of introducing object-oriented concepts, there is no common agreement on how to start such courses. Current study programs often begin by teaching a programming language, instead of focusing on the basics of object-oriented concepts. In the last years a learning environment was developed based on a visual programming language to abstract away from details. It assists teaching step-by-step object-oriented concepts and the syntax and semantics of a programming language in secondary schools and first year university courses. Our goal is to port this learning environment to the widely used IDE Eclipse.

Selective Tracing of Java Programs - Wendehals, Lothar; Meyer, Matthias; Elsner, Andreas (Proc. of the 2nd International Fujaba Days 2004, Darmstadt, Germany)
Design recovery, which means extracting design documents from source code, is usually done by static analysis techniques. Analysing behaviour by static analysis is very imprecise. We combine static and dynamic analysis to increase the preciseness of our design recovery process. In this paper we present an approach to collect data for the dynamic analysis by recording method calls during a program's execution. To reduce the amount of information we monitor only relevant classes and methods identified by static analysis.

Aktuelle Änderungen beim Betriebsausgabenabzug - Geschenke, Bewirtungskosten, Fahrtkostenzuschüsse und Halbjahres-AfA - Sureth-Sloane, Caren; Müller, Jens; Nordhoff, Daniel (BBK - Buchführung, Bilanzierung, Kostenrechnung)

Computability in linear algebra - Ziegler, Martin; Brattka, Vasco (Theoretical Computer Science)

Computable operators on regular sets - Ziegler, Martin (Computability and Complexity in Analysis)
For uniform computability of regular sets in Euclidean space, previous work has identified twelve 'basic' notions, to (pairs of) which many previous notions considered in literature were shown to be equivalent. With respect to those basic notions, we now investigate on the computability of natural OPERATIONS on regular sets: union, intersection, complement, convex hull, image, and pre-image under suitable classes of functions.

Fast Multipoint Evaluation of Bivariate Polynomials - Nüsken, Michael; Ziegler, Martin (Proc. 12th Annual Symposium on Algorithms (ESA'04))
We generalize univariate multipoint evaluation of polynomials of degree n at sublinear amortized cost per point. More precisely, it is shown how to evaluate a bivariate polynomial p of maximum degree less than n, specified by its n^2 coefficients, simultaneously at n^2 given points using a total of O(n^2.667) arithmetic operations. In terms of the input size N being quadratic in n, this amounts to an amortized cost of O(N^0.334) per point.

Spanners, Weak Spanners, and Power Spanners for Wireless Networks - Schindelhauer, Christian; Volbert, Klaus; Ziegler, Martin (Proc. of 15th Annual International Symposium on Algorithms and Computation (ISAAC'04))
For $c in REAL$, a $c$-spanner is a subgraph of a complete Euclidean graph satisfying that between any two vertices there exists a path of weighted length at most $c$ times their geometric distance. Based on this property to approximate a complete weighted graph, sparse spanners have found many applications, e.g., in FPTAS, geometric searching, and radio networks. For geometric searching, it turned out to suffice whether the radius rather than the length of some path between any two vertices is bounded relatively to their geometric distance; this is the defining property of weak spanners. Finally regarding radio network applications, a power spanner accounts for the total energy afforded for a wireless transmission with the requirement that the sum of the squares of the lengths of some path between any two planar vertices must be bounded relatively to the square of their geometric distance (or higher powers up to 6 or even 8). While it is known that any $c$-spanner is also both a weak $C_1$-spanner and a $C_2$-power spanner (for appropriate $C_1,C_2$ depending only on $c$ but not on the graph under consideration), we show that the converse fails: There exists a family of $c_1$-power spanners that are no weak $C$-spanners and also a family of weak $c_2$-spanners that are no $C$-spanners for any fixed $C$ (and thus no uniform spanners, either). However the deepest result of the present work reveals that, surprisingly, any weak spanner is also a uniform power spanner. We further generalize the latter notion by considering $(c,delta)$-power spanners where the sum of the $delta$-th powers of the lengths has to be bounded; so $(cdot,2)$-power spanners coincide with the usual power spanners and $(cdot,1)$-power spanners are classical spanners. Interestingly, these $(cdot,delta)$-power spanners form a strict hierarchy where the above results still hold for any $deltageq2$; some even hold for $delta>1$ while counterexamples reveal others to fail for $delta<2$. In fact we show that in general every self-similar curve of fractal dimension $d>delta$ is no $(C,delta)$-power spanner for any fixed $C$.

Guidance of Users in Interactive 3D-Visualisations of Material Flow Simulations - Mueck, Bengt; Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias; Kortenjan, Michael (Simulation and Visualisation 2004)
The visualisation of manufacturing-processes assists the user in understanding and analysis. Typically he can move free and unguided in a virtual environment which visualizes the entire process. Thus knowledge and conclusions are to some extend acquired on a random base. This article describes the development of a tool, which enables the user to interactively improve significant production processes in the simulation. He moves in a virtual 3D-environment (walkthrough system) and is able to acquire automatically calculated indications for significant processes. At the same time the simulation considers significant objects in a more detailed way. If the viewer is interested in a significant process, he is automatically guided to the relevant location where he can examine the critical situation by modification of the simulation model.

Transcoding von Webinhalten - Oesterdiekhoff, Brigitte (Informatik Spektrum)

Internet Premium Services for Flexible Format Distributed Devices - Oesterdiekhoff, Brigitte (Proceedings of IFIP Working Conference on Distributed and Parallel Embedded Systems (DIPES'04))

Bereichsübergreifendes Toleranzmanagement. Damit es rund läuft - Kretschmer, Ralf; Denzer, Vera; Zimmer, Detmar (QZ - Qualität und Zuverlässigkeit)

Faserverbundwerkstoffe - experimentelle Bestimmung mechanischer Kenngrößen - Koke, Isabel; Funke, Herbert; Ferber, Ferdinand (Posterbeitrag AG Composite)

Integrated Vehicle Dynamics Control Using Active Brake, Steering, and Suspension Systems - Trächtler, Ansgar (Int. J. Vehicle Design)

Verteilte Fahrdynamikregelung mit zeitgesteuerter Architektur am Beispiel des Bosch-Konzeptes VDM - Albert, Amos; Trächtler, Ansgar (13. Aachener Kolloquium Fahrzeug- und Motorentechnik)

Zusammenspiel von regelbaren Feder-/Dämpfersystemen mit ESP - Trächtler, Ansgar (CTI-Konferenz "Federung und Dämpfung")

Integrierte Fahrdynamikregelung mit ESP, aktiver Lenkung und aktivem Fahrwerk - Trächtler, Ansgar (2. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG)

Vehicle Dynamics Management - Benefits of Integrated Control of Active Brake, Active Steering and Active Suspension Systems - Verhagen, Armin; Futterer, Sylvia; Rupprecht, Josef; Trächtler, Ansgar (Proc. FISITA)

Mapping High Quality Textures on an Interactive Globe - Goetz, F.; Boenning, B.; Domik, Gitta (Proc. of The 4th IASTED International Conference on Visualization, Imgaging, and Image Processing)

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Systematic mistuning of bladed disk assemblies with friction contacts - Götting, Florian; Sextro, Walter; Panning, Lars; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
In turbomachinery, friction contacts are widely used to reduce dynamic stresses in turbine blades in order to avoid expensive damages. As a result of energy dissipation in the friction contacts the blade vibration amplitudes are reduced. In case of so-called friction dampers, which are pressed on the platforms of the blades by centrifugal forces, the damping effect can be optimized by varying the damper mass. This optimization can be done by means of a simulation model applying the so-called component mode synthesis and the Harmonic Balance Method to reduce computation time. It is based on the modal description of each substructure. In a real turbine or compressor blading great differences in the magnitude of the individual blade amplitudes occur caused by unavoidable mistuning of all system parameters like contact parameters and natural frequencies of the blades. It may happen that most of the blades experience only small stresses whereas a few blades experience critical stresses. Therefore, it is necessary to consider mistuning for all system parameters to simulate the forced response of bladed disk assemblies with friction contacts. For a mistuned bladed disk the complete system has to be modeled to calculate the dynamic response. In practice, usually the standard deviations instead of the distributions of the system parameters are known. Therefore, Monte-Carlo simulations are necessary to calculate the forced response of the blades for given mean values and standard deviations of the system parameters. To reduce the computational time, an approximate method has been developed and extended for small and moderate standard deviations of the system parameters to calculate the distribution and the envelopes of the frequency response functions for statistically varying system parameters, in the following called statistical mistuning. The approximate method is based on a sensitivity analysis and the assumption of a Weibull distribution of the vibration amplitudes of the blades. Both, the approximate method and the assumption of a Weibull distribution of the vibration amplitudes are validated by Monte-Carlo simulations. By these investigations the influence of different arrangements of the system parameters for given mean values and standard deviations of the vibration amplitudes of the blades can be determined, too. For the present investigations only a small influence of the arrangement of blades with respect to their natural frequencies has been observed. On the other hand, an intentional mistuning of the damper masses and the natural frequencies of the blades in a systematic way, in the following called systematic mistuning, can be investigated to reduce the amplitudes of the system. The simulation results of a systematic mistuning has been validated by a test rig with a rotating bladed disk assembly with friction dampers. The investigations show a good agreement between the simulations and the measurements but only a slight decrease of the maximum amplitudes in case of a systematic mistuning. Copyright {©} 2004 by ASME
Keywords: Friction; Disks

Linear piezoelectric motors and their application - Hemsel, Tobias (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

A novel approach for high power ultrasonic linear motors - Hemsel, Tobias; Mracek, Maik; Wallaschek, Jörg; Vasiljev, Piotr (Ultrasonics Symposium, 2004 IEEE)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable e.g. to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: the electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well organized and controlled to get an optimized drive that is not oversized and costly.
Keywords: drives; electromechanical effects; linear motors; ultrasonic motors; car sunroof; car window; electromechanical behavior; high power ultrasonic linear motors; multiple miniaturized motors; positioning tasks; translatory drive; Costs; Electromagnetic forces; Frequency; Laboratories; Manufacturing; Mechatronics; Micromotors; Ultrasonic imaging; Vibrations; Voltage

Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Design criteria for piezoelectric transformers - Littmann, Walter; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics)

Self configuration of miniature ultrasonic linear motors - Mracek, Maik; Wallaschek, Jörg; Hemsel, Tobias (Proceedings of the 18th International Congress on Acoustics)

Asymmetrical Underplatform Dampers in Gas Turbine Bladings: Theory and Application - Panning, Lars; Popp, Karl; Sextro, Walter; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
During operation, the rotating blades of a gas turbine are subjected to centrifugal forces as well as fluctuating gas forces, resulting in blade vibrations. In addition to material damping, aerodynamical and blade root damping, underplatform dampers are widely used to increase the amount of damping and to decrease blade vibration amplitudes. The friction forces generated by the relative displacements between the underplatform damper and the blade platforms provide a significant amount of energy dissipation. In practice, a number of different underplatform damper designs are applied. Basically, these are wedge dampers with flat contact areas, cylindrical dampers with curved surfaces or asymmetrical dampers with both flat contact surfaces on one side and curved contact surfaces on the other. The latter damper type combines the advantages of both the wedge and the cylindrical damper by preventing the damper from pure rolling on the one hand as it has been observed for cylindrical dampers and on the other hand, avoiding a diverged plane area contact in case of a wedge damper, causing a damper lift-off. This paper will focus on the investigation of cylindrical and asymmetrical underplatform dampers. A comparison between measurements of rotating assemblies in Siemens PG gas turbines (V84.2, V64.3A and V94.3A(2)) under test and real operating conditions with cylindrical and asymmetrical underplatform dampers and the predictions of the developed theoretical model are presented. Special attention is paid to the frequency shift due to the application of an underplatform damper, since in particular for stationary gas turbines, in addition to the amplitude reduction, the accurate prediction of the resonance frequency is of major interest. Copyright {©} 2004 by ASME
Keywords: Dampers; Gas turbines

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Proceedings of "DeLFI 2004: Die 2. e-Learning Fachtagung Informatik", Paderborn (Germany)

Modeling and Development of Multimedia Systems

Proceedings of the 2nd International Conference on Graph Transformations (ICGT 2004), Rome (Italy)

Peer-To-Peer Technology for Interconnecting Web Services in Heterogeneous Networks - Schattkowsky, Tim; Loeser, Christoph; Müller, Wolfgang (Proceedings of the 18th International Conference on Advanced Information Networking and Applications (AINA 2004), Fukuoka (Japan))

Style-Based Refinement of Dynamic Software Architectures - Baresi, Luciano; Heckel, Reiko; Thöne, Sebastian; Varró, Dániel (Proceedings of the conference on Software Architecture (WICSA 2004), Oslo (Norway))

Software Testing via Model Checking - Belli, Fevzi; Güldali, Baris (Proceedings of the conference on Computer and Information Sciences (ISCIS 2004), Kemer-Antalya (Turkey))

Conceptual Modeling of Styles For Mobile Systems: A layered approach based on graph transformation - Heckel, Reiko; Guo, Ping (Proceedings of the conference on Mobile Information Systems (MOBIS 2004), Oslo (Norway))

Application of Graph Transformation for Automating Web Service Discovery - Heckel, Reiko; Cherchago, Alexey (Proceedings of the seminar on Language Engineering for Model-Driven Software Development (2003), Dagstuhl (Germany))

Model-Based Design of Embedded Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of the 7th IEEE International Symposium on Object-Oriented Real-Time Distributed Computing (ISORC 2004), Vienna (Austria))

Specification Matching of Web Services Using Conditional Graph Transformation Rules - Cherchago, Alexey; Heckel, Reiko (Proceedings of the conference on Graph Transformation (ICGT 2004), Rome (Italy))

Automated Data and Service Mapping for Integrated Electronic Markets - Böttcher, Stefan; Groppe, Sven; Schattkowsky, Tim (Proceedings of the 8th World Multi-Conference on Systemics, Cybernetics and Informatics (SCI 2004), Orlando, FL (USA))

An Architecture Description Language for Developing Automotive ECU-Software - Eden, Jonas; Weber, Matthias; Reiser, Mark-Oliver; Wierczoch, Thomas; Freund, Ulrich; Gurrieri, Orazio; Küster, Jochen; Lönn, Henrik; Migge, Jörn (Proceedings of the 14th International Symposium and 4th European Systems Engineering Conference (INCOSE 2004), Toulouse (France))

Guest Editors' Introduction - Engels, Gregor; Sauer, Stefan (International Journal of Software Engineering and Knowledge Engineering (IJSEKE))

Modeling and Simulation of Context-Aware Mobile Systems - Guo, Ping; Heckel, Reiko (Proceedings of the 19th IEEE international conference on Automated software engineering (ASE 2004))

Simulation and Testing of Mobile Computing Systems using Fujaba - Guo, Ping; Heckel, Reiko (Proceedings of the 2nd International Fujaba Days (2004), Darmstadt (Germany))

Model-Based Specification and Execution of Embedded Real-Time Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of the conference on Design Automation and Test in Europe (DATE 2004), Paris, France)

Direct Execution of UML 2.0 Sequence Diagrams - Schattkowsky, Tim (Proceedings of the 10th International Conference on Information Systems Analysis and Synthesis (ISAS 2004), Orlando, FL (USA))

Efficient Execution of UML State Machines on a Virtual Machine - Schattkowsky, Tim (Proceedings of the conference on Systemics, Cybernetics and Informatics (SCI 2004), Orlando, FL (USA))

Model-based Discovery of Web Services - Hendrik Hausmann, Jan; Heckel, Reiko; Lohmann, Marc (Proceedings of the IEEE International Conference on Web Services (ICWS 2004))

Peer-to-Peer-based Web Services for Collaborative Engineering Environments - Schattkowsky, Tim; Loeser, Christoph; Müller, Wolfgang (Proceedings of the International Conference on Networking (ICN 2004), Guadeloupe (France))

Integrated Solar Home System - Krauter, Stefan; Ochs, F. (Renewable Energy)

Considerations for the Calculation of Greenhouse Gas Reduction by Photovoltaic Solar Energy - Krauter, Stefan; Rüther, R. (Renewable Energy Vol. 29, Issue 3 (2004), S. 345–355.)

Development of an integrated solar home system - Krauter, Stefan (Solar Energy Materials & Solar Cells)

Increased electrical yield via water flow over the front of photovoltaic panels - Krauter, Stefan (Solar Energy Materials & Solar Cells)

Remote PV-system monitored via satellite - Krauter, Stefan; Depping, T. (Solar Energy Materials & Solar Cells)

Future Visions - Krauter, Stefan (Words into Action – The International Conference for Renewable Energies – Bonn 2004, Faircount, London (UK), S. 175)

Renewable Energies in Latin America - Krauter, Stefan (Proceedings of the Second World Renewable Energy Forum, Eurosolar, Bonn (Deutschland), 29.–31. Mai 2004)

Enhanced Integrated Solar Home System - Krauter, Stefan (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 2399–2402)

Photovoltaics in the Context of Carbon Trading - Krauter, Stefan (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3523–3526)

Cost Reduction and Increase of Reliability for Remote PV-Systems by Satellite - Krauter, Stefan; Depping, T. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3527–3530)

PV in Combination with Micro Wind Turbines for Rural Household Electrification in the Northeast of Brazil - Krauter, Stefan; Calvacante, F. S. A.; Cunha, M. S.; de Lima, L. C. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3532)

Renewable Energy in Latin America - Krauter, Stefan; Kissel, J. (Renewable Energy World)

Activities concerning the Set-up of an International University for Renewable Energy - Krauter, Stefan (Proceedings of the International Seminar on Hydrogen Technologies, Buenos Aires (Argentina), 7.–9. September 2004)

Security Aspects of Internet Voting - Schryen, Guido (37th Annual Hawaii International Conference on System Sciences)
Voting via the Internet has become a feasible option for political as well as non-political ballots. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. The article starts with a brief presentation of advantages and disadvantages of Internet ballots and presents application fields and pilot schemes. Then, technological security aspects are derived due to democratic basic principles. Especially the applied voting procedures are critical in security terms. Hence, the most relevant cryptographic protocols are presented and their drawbacks and shortcomings are identified. However, this article does not propose a new voting protocol. Beyond fixing cryptographic procedures for ballots, more elements are to be specified, e.g. responsibilities and rights of involved authorities or security precautions regarding hardware and software. For this reason, a structural security framework for electronic voting systems is presented which can be used for their composition and analysis.

Internationalisierung mittelständischer Unternehmen: Fünf Thesen zum Auslandsmarkterfolg - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Brewster, C (Handwörterbuch des Personalwesens)

The Netherlands and Germany: Flexibility or Rigidity - Dietz, B; Hoogendoorn, J; Kabst, Rüdiger; Schmelter, A (Human Resource Management in Europe: Evidence of Convergence?)

Transaktionskostentheorie: Einführung, kritische Diskussion und Ansätze zur Weiterentwicklung - Kabst, Rüdiger (Personaltheorie als Beitrag zur Theorie der Unternehmung)

Theoretical Perspectives for Human Resource Management: The German Discussion - Kabst, Rüdiger; Weber, W (Management Revue: The International Review of Management Studies.)